(untitled) (Revista Logos Ciencia & Tecnología, 2019)
Complexity as a topic of work in science and research has been taking greater boom due to its particular perspective, has three orientations that are the best known, on the one hand are the contributions of complex thinking, another perspective is systemic thinking and the third , theories of complexity from physics, this paper is based on this second line, this perspective provides elements of study such as networks, complex systems and their contributions are applicable to different areas of knowledge, including social sciences. Complexity has been breaking through to show new ways of conceiving phenomena such as societies, communities, new perspectives to generate social transformation using complex networks and principles of complexity, this epistemology gives new paths for scientific thinking in relation to human phenomena and It enables new strategies to intervene in them.